1991
DOI: 10.1103/physrevb.44.575
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect related to the magnetization in pure decagonal Al-Mn phases

Abstract: An anomalous Hall effect is measured in pure decagonal A18OMn20 and A178Mn». We show that the Hall resistivity pH is linear with the magnetization M measured for the same fields and temperatures: pH(H T) =ROH +4wRsM (H T). The very dominant term RsM of p& reveals a strong spin-orbit scattering, which is observed in Al-Mn quasicrystals. Rs is found to be temperature independent in the range 6.5 -110 K. From our susceptibility, specific-heat, and magnetoresistance data, we deduce that M results from a very low f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…(Because of its T −2 dependence, C hyp is only measurable at very low temperature, practically below 300 mK, and thus includes the contribution of the spins frozen in the spin glass interactions when T f 300 mK.) The value of the product x * S 2 deduced in this way has been systematically found to be very small and, so, could be measurable only for the more magnetic AlM n and AlP dM n QC samples [4,16,17]. It is precisely the case where T f 300 mK and where almost all the spins contributing to the Curie constant are involved in the spin glass phase (almost no Kondo spins: See section 4).…”
Section: More On the Fraction Of Magnetic M N Atomsmentioning
confidence: 91%
See 1 more Smart Citation
“…(Because of its T −2 dependence, C hyp is only measurable at very low temperature, practically below 300 mK, and thus includes the contribution of the spins frozen in the spin glass interactions when T f 300 mK.) The value of the product x * S 2 deduced in this way has been systematically found to be very small and, so, could be measurable only for the more magnetic AlM n and AlP dM n QC samples [4,16,17]. It is precisely the case where T f 300 mK and where almost all the spins contributing to the Curie constant are involved in the spin glass phase (almost no Kondo spins: See section 4).…”
Section: More On the Fraction Of Magnetic M N Atomsmentioning
confidence: 91%
“…In practice, this requires an unusual relative precision (much better than 10 −3 ) on M , H, T at low temperature and in weak field conditions [20,22]. The work [22] performed on a melt spun i − Al 73 M n 21 Si 6 QC sample (for which θ = 0) showed that A 3 (T ) and A 5 (T ) vary by orders of magnitude when the temperature is 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 4 Hippert & Préjean [20]) and of an icosahedral AlM nSi QC (from [22]). On this figure, only the T -dependence is significant: The C, A 3 and A 5 data have been arbitrarily vertically shifted to be presented altogether.…”
Section: Spin Glass Transition and Deduction Of The M N Spin Valuementioning
confidence: 99%
“…To our knowledge, the resistivity of AlFe and Al 2 Fe 5 were not still reported in literature. According to Gozlan et al [14], the resistivity of the icosahedral phase Al 82 Fe 18, amounts to 400 mU cm at (À73 C). This value which is close to those obtained in this work (350 mU.cm) for the composition Al 83 Fe 17 supports our assumption on the phase identification.…”
Section: Resistivity Of Alefe Intermediate Phases At Room Temperaturementioning
confidence: 99%
“…The size of the cell is 33 mm in diameter and 60 mm high. The mass of the empty cell is about 50 g and the internal capacity is 50 cm 3 . A platinum resistance thermometer which was made by the Instrument Manufactory of Yunnan, China, and calibrated on the basis of the ITS-90 by the Station of Low Temperature Metrology, Academia Sinica, with an uncertainty of about 1 mK, and a heater assembly were inserted in the central entrant well of the cell.…”
Section: Adiabatic Calorimetrymentioning
confidence: 99%
“…Since its discovery, extensive researches have been carried out to characterize the properties of this new kind of materials [2,3]. However, little has been done on their speci®c heat properties which provide important information about critical and supercritical phenomena.…”
Section: Introductionmentioning
confidence: 99%